2018
DOI: 10.1038/s41408-018-0059-6
|View full text |Cite
|
Sign up to set email alerts
|

Real-world data on prognosis and outcome of primary plasma cell leukemia in the era of novel agents: a multicenter national study by the Greek Myeloma Study Group

Abstract: We have studied the efficacy and the prognostic impact of novel agents in 50 primary plasma cell leukemia (pPCL) patients registered in our database. Eighty percent of patients were treated upfront with novel agent-based combinations; 40% underwent autologous stem cell transplantation (ASCT). Objective response rate was 76; 38% achieved at least very good partial response (≥vgPR) and this correlated significantly with bortezomib-based therapy plus ASCT. At the time of evaluation, 40 patients had died. Early mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 25 publications
7
40
0
1
Order By: Relevance
“…We confirmed that the greatest survival benefit, in terms of both PFS (25 vs 6 months) and OS (36 vs 26 months), was observed among the patients who underwent ASCT, thus validating the role of ASCT as a standard consolidation approach after initial cytoreduction, as previously described . In this light, the promising 6‐month OS (92%) observed in the overall population supports the benefit of combining bortezomib with IMiDs upfront to obtain rapid disease control and enable transplantation‐eligible patients to proceed to ASCT.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…We confirmed that the greatest survival benefit, in terms of both PFS (25 vs 6 months) and OS (36 vs 26 months), was observed among the patients who underwent ASCT, thus validating the role of ASCT as a standard consolidation approach after initial cytoreduction, as previously described . In this light, the promising 6‐month OS (92%) observed in the overall population supports the benefit of combining bortezomib with IMiDs upfront to obtain rapid disease control and enable transplantation‐eligible patients to proceed to ASCT.…”
Section: Discussionsupporting
confidence: 86%
“…In the current study, both the median PFS (20 months) and the median OS (33 months) for the entire population compared favorably with those reported using lenalidomide‐based (15 and 28 months, respectively) and bortezomib‐based (12 and 18 months, respectively) regimens …”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations